2004
DOI: 10.1007/s00441-004-0978-3
|View full text |Cite
|
Sign up to set email alerts
|

Myogenesis during holothurian intestinal regeneration

Abstract: Echinoderms are well known as being able to regenerate body parts and thus provide excellent models for studying regenerative processes in adult organisms. We are interested in intestinal regeneration in the sea cucumber, Holothuria glaberrima, and focus here on the regeneration of intestinal muscle components. We have used immunohistochemical techniques to describe the formation of the intestinal muscle layers. Myoblasts are first observed within the regenerating structure, adjacent to the coelomic epithelia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 29 publications
1
43
2
Order By: Relevance
“…Western blot techniques were similar to those used previously (Murray and García-Arrará s, 2004). In brief, homogenates were prepared from the intestinal tissue of H. glaberrima specimens using a Polytron (Brinkmann Instruments) and two different extraction buffers: (1) phosphate buffered saline (PBS) with protease inhibitors (Calbiochem) or (2) and a phenol/chloroform method (TriReagent, Molecular Research Center).…”
Section: Western Blotsmentioning
confidence: 99%
“…Western blot techniques were similar to those used previously (Murray and García-Arrará s, 2004). In brief, homogenates were prepared from the intestinal tissue of H. glaberrima specimens using a Polytron (Brinkmann Instruments) and two different extraction buffers: (1) phosphate buffered saline (PBS) with protease inhibitors (Calbiochem) or (2) and a phenol/chloroform method (TriReagent, Molecular Research Center).…”
Section: Western Blotsmentioning
confidence: 99%
“…This coincides with a disorganization of the muscle layers of the mesentery (Quiñones et al 2002). In addition, selected markers for myocytes, such as a muscle-specific monoclonal antibody and phalloidin labeling (a toxin that labels the actin filaments present within the muscle cell contractile apparatus), are not found within the regenerating structure during the first days of regeneration and eventually appear as the new intestine is formed (Garcia-Arraras and Greenberg 2001; Murray and García-Arrarás 2004). These results suggest that the myocytes close to and within the regenerating structure undergo dramatic changes during the first few weeks of regeneration.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have shown that regeneration of the intestinal system begins from a series of thickenings that are formed at the remaining free edge of the lateral and ventral mesenteries after evisceration and proceeds until it is complete in 3-4 weeks (García-Arrarás et al 1998, 1999. The thickenings eventually give rise to a blastema-like structure, and various processes are associated with its formation, including cell division, migration of various cell populations from the esophagus, cloaca, and mesenteries, and changes in the extracellular matrix components of the connective tissue (García-Arrarás et al 1998, 1999García-Arrarás and Greenberg 2001;Quiñones et al 2002;Murray and García-Arrarás 2004).…”
Section: Introductionmentioning
confidence: 98%
“…See web site for date of publication (http://physiolgenomics.physiology.org). 11,39), little is known about the genes involved. Previous attempts to identify the genes associated with intestinal regeneration in H. glaberrima have been made in our laboratory using a gene by gene strategy, which is time consuming and provided limited information (37,49,51).…”
mentioning
confidence: 99%